The mechanical response of additively manufactured IN625 thin-walled structures. (December 2021) - Banerjee, Arunima; Messina, Sara; Begley, Matthew R.; Schwalbach, Edwin J.; Groeber, Michael A.; Musinski, William D.; Shade, Paul A.; Cox, Marie E.; Miller, Jonathan D.; Hemker, Kevin J.
Abstract: Additive manufacturing offers enhanced design and topological complexity over traditional manufacturing and is well suited to fabricate complex structures. Here, we present a new milli-scale test method to assess the location-specific mechanical response of laser powder-bed printed Inconel 625 thin-walled structures. High-resolution digital image correlation was coupled with ambient temperature milli-scale tests to understand the progression of plastic deformation in T-shaped specimens. Plastic strains were concentrated around the intersection of the horizontal and vertical ligaments, emphasizing their importance in the design process. EBSD scans elucidated the role of geometry in the development of in-plane texture. Isotropic finite element models were unable to fully predict the response of printed specimens, but anisotropic models, motivated by the texture measurements, resulted in much better agreement. This work illustrates the importance of local processing and microstructure on the mechanical response of additively manufactured components. Graphical abstract: Image, graphical abstract